Students’ Academic Vocabulary Mastery : A Descriptive Study at English Language Education of FKIP-UIR - Yulianto Yulianto; Marhamah Marhamah; Johari Afrizal (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2022)
This research aims to describe of the students’ academic vocabulary mastery of the first year students of English Language Education of FKIP-UIR Pekanbaru. The research is descriptive method with data interpretation. The test of this research uses multiple measures to assess three levels of vocabulary knowledge: meaning recognition, written form recall aided by initial letter, and matching exercise. The result of data analysis showed that meaning recognition test the average score is 54,16, and it is classified into poor to average level of mastery. In the written form recall aided by initial letter test, the average score is in the 57,5 and it is classified into poor to average level of mastery. While in the matching exercise, the average score is in 62,08, and it falls into the average to good level of mastery category. The conclusion to the classification of students’ score in academic vocabulary mastery by using AWL test is 57,91 and it is classified into poor to average.